Front Cover. Issue 4 (12th April 2021) - Li, Meng; Jansson, Samuel; Runemark, Anna; Peterson, Jonathan; Kirkeby, Carsten Thure; Jönsson, Anna Maria; Brydegaard, Mikkel
Abstract: European spruce bark beetle, Ips typographus, causing extensive damage to the spruce forest and timber values. Precise monitoring of these beetles is a necessary step towards preventing outbreaks. In this work, light scattering from beetles is characterized, and the feasibility of entomological lidar as a tool for long‐term monitoring of bark beetles is explored. Further details can be found in the article by Meng Li, Samuel Jansson, Anna Runemark, Jonathan Peterson, Carsten Thure Kirkeby, Anna Maria Jönsson, and Mikkel Brydegaard (e202000420 ). Abstract : European spruce bark beetle, Ips typographus, causing extensive damage to the spruce forest and timber values. Precise monitoring of these beetles is a necessary step towards preventing outbreaks. In this work, light scattering from beetles is characterized, and the feasibility of entomological lidar as a tool for long‐term monitoring of bark beetles is explored. Further details can be found in the article by Meng Li, Samuel Jansson, Anna Runemark, Jonathan Peterson, Carsten Thure Kirkeby, Anna Maria Jönsson, and Mikkel Brydegaard (e202000420 ).